Islamic Finance and Accounting in the UK: Strategic Intersections for Economic, Social and Political Perspectives - BQ.WARIKATUL HAFIZAH; Dr. Emir Camdzic PhD (IRTIQO' : Postgraduate Journal of Islamic Economics, Finance and Accounting Studies, 2026)
This study aims to analyse challenges and opportunities for the implementation of Islamic accounting in the Islamic financial industry in the UK through the case study of Al Rayan Bank, with the particular focus on economic, social, and political perspective. This study uses an exploratory qualitative approach with content analysis to assess the challenges and opportunities for implementing Islamic accounting through a case study of Al Rayan Bank. Islamic financial institutions in the UK face challenges in aligning accounting standards between AAOIFI and IFRS, which have an impact on the transparency of financial statements and the competitiveness of Islamic banking in the global market both from a socio-economic and political perspective. This paper emphasizes the alignment of Islamic accounting standards by looking at the social, political, and economic aspects in the UK.